2019
DOI: 10.1155/2019/3583250
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vitamin D Level and Vitamin D Receptor Polymorphism in Hypothyroid Egyptian Patients

Abstract: Purpose. The current study aimed at assessing vitamin D level and vitamin D receptor polymorphism in hypothyroid Egyptian patients and its effect on hypothyroidism and thyroid morphology, also to find a causal relation between vitamin D and hypothyroidism. Methods. This case-control study was conducted on 35 hypothyroid patients and 35 matched unrelated healthy controls. Total serum 25-hydroxyvitamin D3 and thyroid antibodies were measured using a human ELISA kit. Genotyping was performed by using real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Three years later, Camurdan et al observed that hypovitaminosis D rate was higher in children with HT compared to control group (73.1% vs. 17.6%) and confirmed the inverse association between 25(OH)D3 levels and TPOAb titer in their pediatric population [71]. This inverse correlation was substantiated in the following studies: [66,[72][73][74][75]. Furthermore, different clinical studies showed that the prevalence of HT in patients with hypovitaminosis D was significantly higher than that documented in subjects with sufficient vitamin D levels, particularly among children, elderly subjects, and pre-menopausal women [64,71,[76][77][78][79][80][81].…”
Section: Hashimoto's Thyroiditismentioning
confidence: 75%
“…Three years later, Camurdan et al observed that hypovitaminosis D rate was higher in children with HT compared to control group (73.1% vs. 17.6%) and confirmed the inverse association between 25(OH)D3 levels and TPOAb titer in their pediatric population [71]. This inverse correlation was substantiated in the following studies: [66,[72][73][74][75]. Furthermore, different clinical studies showed that the prevalence of HT in patients with hypovitaminosis D was significantly higher than that documented in subjects with sufficient vitamin D levels, particularly among children, elderly subjects, and pre-menopausal women [64,71,[76][77][78][79][80][81].…”
Section: Hashimoto's Thyroiditismentioning
confidence: 75%
“…In our study, we found that the odds of developing hypothyroidism were significantly higher among patients with intermediate and deficient levels of vitamin D. Kim 38 reported in Korean population that vitamin D deficiency is highly prevalent in autoimmune Hashimoto’s thyroiditis presenting with overt hypothyroidism than subclinical hypothyroid variants [ 38 ]. Studies have shown that a reciprocal relationship exists between serum TSH and vitamin D levels in hypothyroid subjects [ 38 , 39 ]. ElRawi et al reported vitamin D deficient hypothyroid subjects have higher insulin resistance which significantly correlated with higher anti-thyroid antibodies, anti-TPO and anti-Tg [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a reciprocal relationship exists between serum TSH and vitamin D levels in hypothyroid subjects [ 38 , 39 ]. ElRawi et al reported vitamin D deficient hypothyroid subjects have higher insulin resistance which significantly correlated with higher anti-thyroid antibodies, anti-TPO and anti-Tg [ 39 ]. However, they did not observe any significant vitamin D receptor polymorphism in subject vs control suggesting that correction with vitamin D supplements may possibly have a therapeutic benefit in correcting thyroid status.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, no significant association was found between Vitamin D levels and FokI polymorphism among major depression patients [31]. In a study evaluating 84 pediatric patients with a diagnosis of Hashimoto's Thyroiditis, VDR polymorphisms and vitamin D levels were not related [32,33].…”
Section: Discussionmentioning
confidence: 99%